1988
DOI: 10.1093/nar/16.9.3671
|View full text |Cite
|
Sign up to set email alerts
|

Ligation of oligonucleotides to nucleic acids or proteins via disulfide bonds

Abstract: We have developed general methods for joining together, via cleavable disulfide bonds, either two unprotected polynucleotides or a polynucleotide and a peptide or protein. To join two oligonucleotides, each is first converted to an adduct in which cystamine is joined to the 5'-terminal phosphate of the oligonucleotide by a phosphoramidate bond. The adducts are mixed and reduced with dithiothreitol. The dithiothreitol is then removed by dialysis. Oxidation by atmospheric oxygen occurs to yield the required dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…The single-strand polynucleotide was phosphorylated with T4 polynucleotide kinase, as described by Maniatis et al (9). Cystamine was added to the 5' end of the single-stranded (ss) polynucleotide as described by Chu and Orgel (12), and the product was purified as described by Teare and Wollenzien (13). Typically :20 ,ug of phosphorylated ss DNA in 20 ,ul of water was mixed with 40 1.l of 1 M Abbreviations: ss, single-stranded; ds, double-stranded; CRP, cAMP receptor protein; CPM, 7-diethylamino-3-(4'-maleimidylphenyl)-4-methylcoumarin; 32-bp-CPM, 32-bp fragment of lac promoter DNA labeled with CPM at the 5' end.…”
Section: Methodsmentioning
confidence: 99%
“…The single-strand polynucleotide was phosphorylated with T4 polynucleotide kinase, as described by Maniatis et al (9). Cystamine was added to the 5' end of the single-stranded (ss) polynucleotide as described by Chu and Orgel (12), and the product was purified as described by Teare and Wollenzien (13). Typically :20 ,ug of phosphorylated ss DNA in 20 ,ul of water was mixed with 40 1.l of 1 M Abbreviations: ss, single-stranded; ds, double-stranded; CRP, cAMP receptor protein; CPM, 7-diethylamino-3-(4'-maleimidylphenyl)-4-methylcoumarin; 32-bp-CPM, 32-bp fragment of lac promoter DNA labeled with CPM at the 5' end.…”
Section: Methodsmentioning
confidence: 99%
“…Disulfide coupling chemistry has been used in the ligation of peptide to peptide (37), DNA to DNA (37), peptide to DNA (37), DNA to haptens (36), DNA to paramagnetic beads (15), and DNA to controlled porosity glass (CPG) 2 (35). Here, we report a simple, efficient, and specific attachment chemistry utilizing the disulfide bond for the covalent immobilization of presynthesized DNA probes onto a silane-derivatized glass support.…”
mentioning
confidence: 99%
“…Both the azide and alkyne SAMs are expected to make the slide surface highly hydrophobic, and thus help to prevent nonspecific interactions with the glass surface. Both the click chemistry and the thiol approaches have been previously shown to be compatible with downstream processing 13. 14 We found that the click chemistry approach with the alkyne‐functionalized surface was the less time consuming and required fewer materials.…”
Section: Methodsmentioning
confidence: 83%